Dikesavståndets inverkan på såtid och skörd - Tornerhjelm, Hilding (2014)
All arable land in Sweden need a proper drainage for an effectively agriculture to take place. Of all arable land in Sweden, about 50% is naturally drained and 50% need artificial drainge. More than half of the tile drained area is in need of new drainage or renewed drainage. A good drainage improves farming and crop growth and increases the opportunity to achieve a high and safe harvest level. Future climate change and agriculture size rationalization will increase the need for good drainage. In this paper, two trials with three drainage distances, performed at Lanna experimental station, were analyzed using a mixed linear model. For the spring crops barley and oats, the objectives were to examine how subsurface drainage at the drain spacings of 16 m, 32 m and 80 m affects harvest level and optimal seeding date. For winter wheat, the objective was only to investigate how the drain spacings impact harvest level. The analysis gave significant results for oats, where the drain distances of 16 and 32 m gave a yield increase compared to 80 m Wheat gave a significant yield increase for 16 m drain spacing as compared to 80 m. For barley, no significant differences were found between the drain spacings. Furthermore, oat yields were significantly different for all sowing dates, where early sowing dates gave the highest yields. Barley gave significantly lower yield for late sowing dates.